A systematic review of leukocyte telomere length and age in adults - Müezzinler, Aysel; Dieffenbach, Aida Karina; Brenner, Hermann (Ageing research reviews, 2013)
Objective - To provide a systematic review of the relationship between age and leukocyte telomere length (LTL) in adults. - Methods - Relevant studies were identified by a systematic search of Medline, EMBASE and ISI Web of Knowledge databases. Key data, such as age and LTL, were extracted from the studies along with correlation coefficients and yearly attrition rates where available. Obtained data were used to calculate weighted means and correlation coefficients. - Results - Overall, 124 cross-sectional studies and 5 longitudinal studies were identified. A statistically significant inverse correlation between mean age and mean LTL across cross-sectional studies was observed for both absolute (r=−0.338, p<0.0001) and relative LTL (r=−0.295, p=0.0088). From mean LTL and ages, a yearly telomere loss of 24.7 base pairs (BP)/year was estimated by weighted linear regression. Weighted means of within study correlation of age and TL and yearly telomere loss rate estimates from cross-sectional studies were also in a similar order of magnitude (−0.380 and 21.91BP/year). The few longitudinal studies reported somewhat higher mean telomere loss rates (between 32.2 and 45.5BP/year). - Conclusion - While a decrease of LTL with age is out of question, data on variation of the decrease according to sex, age and other potential determinants especially from longitudinal data are still sparse.